The Correlations between the Intensity of Histopathological Ubiquitin-Specific Protease 11 Staining and Progression of Prostate Cancer - Jae Heon Kim; Hee Jo Yang; Kwang Woo Lee; Jae Joon Park; Chang-Ho Lee; Youn Soo Jeon; Jae Ho Kim; Suyeon Park; Su Jung Song; Ji-Hye Lee; Ahrim Moon; Yon Hee Kim; et al. (MDPI AG, 2023)
Background: Ubiquitin-specific protease 11 (USP11), one of the principal phosphatase and tensin homolog (PTEN) deubiquitinases, can reserve PTEN polyubiquitination to maintain PTEN protein integrity and inhibit PI3K/AKT pathway activation. The aim of the current study was to investigate the associations between immunohistochemical USP11 staining intensities and prognostic indicators in individuals with prostate cancer. Methods: Tissue microarrays (TMAs) were performed for human prostate cancer and normal tissue (control) samples. Data on patient's age, Gleason score, plasma prostate-specific antigen (PSA) titer, disease stage, and presence of seminal vesicles, lymph nodes, and surgical margin involvement were collected. A pathologist who was blinded to the clinical outcome data scored the TMA for USP11 staining intensity as either positive or negative. Results: Cancerous tissues exhibited lower USP11 staining intensity, whereas the neighboring benign peri-tumoral tissues showed higher USP11 staining intensity. The degree of USP11 staining intensity was lower in patients with a higher PSA titer, higher Gleason score, or more advanced disease stage. Patients who showed positive USP11 staining were more likely to have more optimal clinical and biochemical recurrence-free survival statistics. Conclusions: USP11 staining intensity in patients with prostate cancer is negatively associated with several prognostic factors such as an elevated PSA titer and a high Gleason score. It also reflects both biochemical and clinical recurrence-free survival in such patients. Thus, USP11 staining is a valuable prognostic factor in patients with prostate cancer.